STUDY OF HUMAN RESOURCE ACCOUNTING PRACTICES- AN OVERVIEW - Johar, Damandeep; Sridhar, Dr. P.; Roopalatha, Dr. N. (The journal of contemporary issues in business and government, 2022)
Human Resource Accounting (HRA) was introduced in 1980s, it is the process of identifying, communicating, and measuring data about human resources. It is highly complicated in today’s market to find well knowledge, and highly motivated people. But human resource is one of the most important operations for any organization or business. Without the human involvement can lose its efficiency in work, and all the areas of business and levels human efficiency is required with machine efficiency. Thus, companies have to recognize and appreciate the value of their employees. It is worth and capital investments. The objective of this paper is to study the human resources accounting practices, to identify challenges and issues, and to give suggestions based on the findings of the study.